Analysis of Student Learning Style in IPAS Learning with a Differentiated Learning Approach as an Optimization of the MerdekaCurriculum at Elementary School - lestari, Mutiara Intan Lestari; Ichsan Anshory; Arinta Rezty Wijayaningputri; Mutiara Intan Lestari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to determine the role of learning styles in differentiated learning in IPAS learning as an optimization of the Merdeka curriculum. The number of informants in this study was four, consisting of one fourth-grade teacher and three fourth-grade students. This type of research uses descriptive qualitative methods, data collection through interviews with grade IV teachers and three students with different learning styles, observation in learning, learning style questionnaires to grade IV students, and documentation. Data validity test using triangulation techniques and sources. Data analysis techniques follow the Miles and Huberman procedure, which has three methods: data reduction in the context of this study in the form of interview results, observations, and learning style questionnaire results, presentation of data from the reduction results presented in the form of descriptive tables and narratives, the last is concluding. The findings of the analysis show that learning styles have a significant effect on the achievement of learning objectives through a differentiated approach. Several learning styles were identified after being given a learning style questionnaire to class IV students. The results show that the majority of students have a visual learning style (58%), kinesthetic learning style (28%), and auditory learning style (18%). By applying the four aspects and steps of differentiated learning, learning is more focused and enjoyable for students. This can increase students' motivation and engagement in learning and help them achieve better academic results. This research contributes to developing more effective learning strategies in the independent curriculum. Differentiated learning serves as a bridge to create a learning experience that suits students' interests and needs by customizing methods based on learning styles. It also helps improve the effectiveness of the learning process by paying attention to each student's learning preferences.